Soil organic carbon dynamics and crop yield for different crop rotations in a degraded ferruginous tropical soil in a semi-arid region: a simulation approach - Soler, C.M.T.; Bado, V.B.; Traoré, K.; Bostick, W.M.; Jones, J.W.; Hoogenboom, G. (Cambridge University Press, 2011)
In recent years, simulation models have been used as a complementary tool for research and forquantifying soil carbon sequestration under widely varying conditions. This has improved theunderstanding and prediction of soil organic carbon (SOC) dynamics and crop yield responses to soiland climate conditions and crop management scenarios. The goal of the present study was to estimatethe changes in SOC for different cropping systems in West Africa using a simulation model. A croprotation experiment conducted in Farakô-Ba, Burkina Faso was used to evaluate the performance ofthe cropping system model (CSM) of the Decision Support System for Agrotechnology Transfer(DSSAT) for simulating yield of different crops. Eight crop rotations that included cotton, sorghum,peanut, maize and fallow, and three different management scenarios, one without N (control), onewith chemical fertilizer (N) and one with manure applications, were studied. The CSM was able tosimulate the yield trends of various crops, with inconsistencies for a few years. The simulated SOCincreased slightly across the years for the sorghum–fallow rotation with manure application. However,SOC decreased for all other rotations except for the continuous fallow (native grassland), in which theSOC remained stable. The model simulated SOC for the continuous fallow system with a high degreeof accuracy normalized root mean square error (RMSE)= 0·001, while for the other crop rotations thesimulated SOC values were generally within the standard deviation (S.D.) range of the observed data.The crop rotations that included a supplemental N-fertilizer or manure application showed an increasein the average simulated aboveground biomass for all crops. The incorporation of this biomass into thesoil after harvest reduced the loss of SOC. In the present study, the observed SOC data were used forcharacterization of production systems with different SOC dynamics. Following careful evaluation ofthe CSM with observed soil organic matter (SOM) data similar to the study presented here, thereare many opportunities for the application of the CSM for carbon sequestration and resourcemanagement in Sub-Saharan Africa